The role of intraoperative transesophageal echocardiography in the management of renal cell carcinoma with atrial thrombus – case report - Łukasz Trzciniecki Maciej; Bursiewicz Wiktor; Trzciniecka Monika; Mączka Krystian; Legieć Mikołaj; Sobieraj Jakub; Kowal Paweł (Journal of Ultrasonography, 2023)
Renal cell carcinoma is a common disease, and clear cell renal cell carcinoma is the most common histological type. Renal cell carcinoma has a tendency to infiltrate the venous system including the inferior vena cava and the right atrium of the heart. We present the cases of two patients with renal cell carcinoma with stage IV tumor thrombus according to the Mayo classification, who underwent surgery under transesophageal echocardiography guidance. Apart from standard imaging methods used in renal cancer with tumor thrombus reaching the right atrium of the heart, we consider transesophageal echocardiography to be a very useful tool in the diagnostic work-up, patient monitoring, and selection of appropriate surgical technique.